Digitalizing makhārij al-ḥurūf: Leveraging Praat for English Pronunciation Improvement in Islamic Education - Maskur; Azizah; Fithriyah (Barkah Publishing, 2024)
This research investigates the integration of Praat technology with makhārij al-ḥurūf to enhance English pronunciation skills among students of Islamic education. The primary objective is to assist students in differentiating between long and short vowels in English through acoustic analysis using Praat, with a particular focus on duration and formant visualization. By addressing nuanced phonemic distinctions, such as the contrasts between